2021
DOI: 10.26444/aaem/122682
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between antibiotic resistance, biofilm formation, genes coding virulence factors and source of origin of <i>Pseudomonas aeruginosa</i> clinical strains

Abstract: Introduction and objective. Pseudomonas aeruginosa is an opportunistic pathogen that causes difficult with treating infections, especially in the immunocompromised and patients with some underlying disease. The aim of the study is to assess the antibiotic resistance, biofilm formation, and the presence of genes encoding various virulence factors in clinical isolates of P. aeruginosa. Materials and methods. Seventy-three clinical isolates of Pseudomonas aeruginosa were tested. Antimicrobial Susceptibility Testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 31 publications
4
16
0
Order By: Relevance
“…In contrast, we defined the antibiotic susceptibility of the different isolates before biofilm production, and associated the susceptibility profile with the biofilm-forming capacity. Similar findings were reported in other bacterial species ( Arciola et al, 2005 ; Klingenberg et al, 2005 ; de Araujo et al, 2006 ; Agarwal and Jain, 2012 ; Yekani et al, 2017 ; Ratajczak et al, 2021 ). For example, Staphylococcus epidermidis strains that produced exopolysaccharide had a significantly higher prevalence of resistance to aminoglycosides, sulfamethoxazole and ciprofloxacin, compared to non-producing isolates.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, we defined the antibiotic susceptibility of the different isolates before biofilm production, and associated the susceptibility profile with the biofilm-forming capacity. Similar findings were reported in other bacterial species ( Arciola et al, 2005 ; Klingenberg et al, 2005 ; de Araujo et al, 2006 ; Agarwal and Jain, 2012 ; Yekani et al, 2017 ; Ratajczak et al, 2021 ). For example, Staphylococcus epidermidis strains that produced exopolysaccharide had a significantly higher prevalence of resistance to aminoglycosides, sulfamethoxazole and ciprofloxacin, compared to non-producing isolates.…”
Section: Discussionsupporting
confidence: 88%
“… 4 In this study, 54 carbapenem-resistant Pseudomonas aeruginosa strains were isolated from patients in the burn ward. P. aeruginosa poses complex acquired and intrinsic carbapenem resistance mechanisms, 17 , 18 which significantly limits the clinician’s choices for antimicrobial selection and treatments. 19 Therefore, burn patients infected by carbapenem-resistant P. aeruginosa are at higher risk of infection complications.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Elmouaden et al [ 16 ] also reported high proportions of the lasB gene among both MDR strains (99%) and MDS strains (97.6%). In addition, Ratajczak et al [ 17 ] reported the leading contribution of the lasB gene among the majority of the P. aeruginosa strains tested (93.1%). Similar findings were reported in the study conducted by Dawodeyah et al [ 18 ], which revealed that all the MDR strains contained the lasB gene.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in their study, Sonbol et al [ 38 ] showed a correlation between the occurrence of virulence genes and the resistance mechanisms. Other reports also suggest the high plasticity of the P. aeruginosa genome, providing evidence for the replacement of genes encoding virulence factors with those showing antibiotic resistance or the opposite [ 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%